Development of a STEAM Based Science Busy Book to Enhance Early Childhood Cognitive Development - Ashadi, Firman; Zahro, Ianatuz; Siswono, Hendrik; Trianggono, Mochammad Maulana (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to develop a STEAM (Science, Technology, Engineering, Arts, and Mathematics)-based Science Busy Book as an innovative learning medium for early childhood education. The research employed a Research and Development (R&D) method using the ADDIE model, comprising the stages of analysis, design, development, implementation, and evaluation. The research instruments included validation sheets, observation checklists, questionnaires, and simple cognitive tests, which were analyzed using quantitative techniques (mean scores and percentages) and qualitative procedures involving data reduction, data display, and conclusion drawing. The results showed that the Busy Book was effective in enhancing children’s engagement and cognitive development. The integration of science, technology, engineering, arts, and mathematics enabled children to participate in exploration, simple experiments, and creative activities. Teachers reported that the medium facilitated instruction and made abstract concepts more accessible. In conclusion, the STEAM-based Science Busy Book is feasible, valid, and effective as an early childhood learning medium, supporting the development of scientific literacy in an interactive and meaningful way.